Editorial: Relevance Theory and Intercultural Communication Problems - Piskorska, Agnieszka (Research in Language, 2017)
This editorial to the special issue of RiL dedicated to relevance theory and problems of intercultural communication addresses the general requirements that a theory of communication must meet to be applicable to the analysis of intercultural communication. Then it discusses criticism levelled against Grice’s theory of conversational implicature and Brown and Levinson’s theory of politeness on the grounds that these theories were not universal enough to be applied to all data. Finally, it offers some remarks on the applicability of relevance theory to intercultural pragmatics.